ISLAMIC REFORM MOVEMENT IN INDONESIA AND BEYOND: Progress and Regress (State Islamic University (UIN) of Sunan Ampel Surabaya, 2008)
This paper is an attempt to review the Islamic reform agendas that have been set by Muslims reformists since the last century. Islamic reform movement has developed and spread from the Middle East to many Muslim countries in the world. Indonesia where Muslims represent the largest population enthusiastically welcomes such a movement. From Minangkabau in West Sumatra, Islamic reform movement then spreads into other areas in the country. It deals with issues that baffled modern Muslims, such as democracy, freedom, pluralism, and secularism. There are some progress and regress in how Muslims respond to those issues. In this article, I address four issues Muslim reformists discussed throughout the decades, namely: Islamic polity, women’s rights, religious freedom, and freedom of expression.